Research methodology and consultancy techniques - Mlowe, L. K (National Board of Accountant and Auditors (NBAA), 2012)
This book has been written in order to help those students who are first timers in Research and Consultancy Assignments. Although it has been prepared purposely as certain target group, it can also be used by others who are interested in research work and consultancy assignment, particularly in Tanzania where the scarcity of research and in particular, consultancy books is more of a norm an exception. In recent years though there has been a tendency for intellectuals/academician to do more consultancy assigment rather than research work, possibly, because of the nature and tedious demands involved in research. it should however be underscored that both research and consultancy go together for the purpose of intellectual development and achievements. It is the hope and conviction of the authors that the book will add some ingredients in the knowledge industries, although by no means in ground breaking way.